2022
DOI: 10.3390/plants11243411
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacteria Application Ameliorates Floral Traits and Outcrossing Rate in Diverse Rice Cytoplasmic Male Sterile Lines

Abstract: In rice, cytoplasmic male sterility (CMS) represents an irreplaceable strategy for producing high-yielding hybrid rice based on the commercial exploitation of heterosis. Thereupon, enhancing floral traits and outcrossing rates in CMS lines increase hybrid seed production and ensure global food security. The exogenous application of cyanobacteria could enhance outcrossing rates in CMS lines and, accordingly, hybrid rice seed production. In the present study, we aimed at exploring the impact of cyanobacteria imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Furthermore, the PCA-biplot and cluster-heatmap analyses indicated that some of the tomato accessions were salt-tolerant (i.e., Subarctic, Raad-Red, Naqeeb, Pakit, Tommy-Toe, and BL-1076) [49]. The combination of cyanobacteria with the promising cytoplasmic male sterility (CMS) lines is considered a useful tool for enhancing the outcrossing rates and improving the seed production of hybrid rice [51].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the PCA-biplot and cluster-heatmap analyses indicated that some of the tomato accessions were salt-tolerant (i.e., Subarctic, Raad-Red, Naqeeb, Pakit, Tommy-Toe, and BL-1076) [49]. The combination of cyanobacteria with the promising cytoplasmic male sterility (CMS) lines is considered a useful tool for enhancing the outcrossing rates and improving the seed production of hybrid rice [51].…”
Section: Discussionmentioning
confidence: 99%
“…This method simplifies and enhances the breeding process [ 72 ]. Moreover, exogenous cyanobacteria applications such as Nostoc muscorum and Anabaena oryzae enhance the outcrossing rates and floral traits, as well as the production of seeds for hybrid rice [ 73 ].…”
Section: Breeding Techniques For Producing Hybrid Ricementioning
confidence: 99%
“…It is possible to achieve this through the implementation of a staggered planting technique (Gaballah et al, 2022;Yanning et al, 2021;Casco et al, 2021). The CMS parent and restorer lines were planted using a certain row ratio and spacing to maximize seed output in producing hybrid rice seeds (Hamad et al, 2022). Considering the previously mentioned aspects, the current study has main goal to standardize the appropriate row ratio for enhancing their outcrossing rate, which could result in higher seed yield, as well as to investigate the optimal plant spacing to increase the population of the female parent for enhancing HIPA18 hybrid rice seed production.…”
Section: Introductionmentioning
confidence: 99%